Use of non-invasive stimulation in movement disorders: a critical review - Godeiro Junior, Clécio de Oliveira (2021)
Background: Noninvasive stimulation has been widely used in the past 30 years to study and treat a large number of neurological diseases, including movement disorders. Objective: In this critical review, we illustrate the rationale for use of these techniques in movement disorders and summarize the best medical evidence based on the main clinical trials performed to date. Methods: A nationally representative group of experts performed a comprehensive review of the literature in order to analyze the key clinical decision-making factors driving transcranial magnetic stimulation (TMS) and transcranial direct current stimulation (tDCS) in movement disorders. Classes of evidence and recommendations were described for each disease. Results: Despite unavoidable heterogeneities and low effect size, TMS is likely to be effective for treating motor symptoms and depression in Parkinson’s disease (PD). The efficacy in other movement disorders is unclear. TMS is possibly effective for focal hand dystonia, essential tremor and cerebellar ataxia. Additionally, it is likely to be ineffective in reducing tics in Tourette syndrome. Lastly, tDCS is likely to be effective in improving gait in PD. Conclusions: There is encouraging evidence for the use of noninvasive stimulation on a subset of symptoms in selected movement disorders, although the means to optimize protocols for improving positive outcomes in routine clinical practice remain undetermined. Similarly, the best stimulation paradigms and responder profile need to be investigated in large clinical trials with established therapeutic and assessment paradigms that could also allow genuine long-term benefits to be determined.